The American Chemical Society and its Activities in Latin America - Miller, Bradley D. (2004)
The purpose of this article is to provide information about and examples of ACS activities in Latín America, notably those which have taken place in partnership with the Federation of Latín American Chemical Associations (FLAQ) and its member-nation chemical societies.